A novel design of thermoelectric generator for automotive waste heat recovery - Huang, Kuo; Yan, Yuying; Li, Bo; Li, Yong; Li, Kai; Li, Jun (Springer, 2018)
With progressively stringent fuel consumption regulations, many researchers and engineers are focusing on the employment of waste heat recovery technologies for automotive applications. Regarded as a promising method of waste heat recovery, the thermoelectric generator (TEG) has been given increasing attention over the whole automotive industry for the last decade. In this study, we first give a brief review of improvements in thermoelectric materials and heat exchangers for TEG systems. We then present a novel design for a concentric cylindrical TEG system that addresses the existing weaknesses of the heat exchanger. In place of the typical square-shaped thermoelectric module, our proposed concentric cylindrical TEG system uses an annular thermoelectric module and employs the advantages of the heat pipe to enhance the heat transfer in the radial direction. The simulations we carried out to verify the performance of the proposed system showed better power output among the existing TEG system, and a comparison of water-inside and gas-inside arrangements showed that the water-inside concentric cylindrical TEG system produced a higher power output.